Optimizing the Role of Supervising Teachers Through Small Groups and Peer Tutors Tutoring Teaching Types to Strengthen the Character, Spirituality, Academics and Discipline (KSAD) of Students at SMAN 1 Asam Jujuhan, Dharmasraya Regency - Yanti, Efrita (The Future of Education Journal, 2023)
The low level of application of character values ​​and religious values ​​by school members, such as the rise of dishonesty in the National Examination (UN), fights between students or between schools, sexual abuse by students against their own friends, the rise of pornographic videos. This can be overcome through the character of education, so that the goal of national education can be achieved, namely a nation that is intelligent and has noble morals and becomes a complete human being. The aim of this school action research is to explain the implementation of the peer tutoring learning model with small groups. Tutoring teaching type in strengthening Academic and Disciplinary Spiritual Character (KSAD) values ​​through National Development Character Group activities for students at SMAN 1 Asam Jujuhan. This type of research is School Action Research which consists of 2 cycles with a span of 2 months. Cycle I lasted for 3 meetings at SMAN 1 Asam Jujuhan. Cycle II started the same activity, namely 3 meetings at SMAN 1 Asam Jujuhan, with the same material and treatment). The results of the study show that the results of the KSAD guidance of students have increased. In several indicators of student attendance, it showed a very different increase from cycle I to cycle II. The increase in the results of student Army Chief of Staff guidance shows that the small group learning method and peer tutoring with the tutoring type of learning have succeeded in making students motivated to apply character, spiritual, academic and disciplinary values, although not all children are successful in this guidance